Domestic Politics and Strategic Culture: The 2023 Russian Security Policy Shift on New START - Moh Nasir (Politicon : Jurnal Ilmu Politik, 2024)
Russia and the United States have been in the New START agreement for 13 years. A year before the agreement expired, the two countries agreed to extend the agreement until 2026. However, in early 2023, Russia officially announced that it was temporarily stopping its involvement in the New START agreement. This article uses the neoclassical realism analytical framework from Ripsman et.al. This article was prepared using a qualitative-deductive approach. Supported by primary data sources which include official state documents and statements by state officials and secondary sources in the form of scientific works, expert opinions and sources from third parties. The data is processed based on illustrative analysis. The findings in this article are that Russia's withdrawal from the New START agreement was caused by changes in the security environment caused by the US; Vladimir Putin's aggressive personality; a Russian form of government that gives the president full authority over his foreign policy; and Russia's strategic culture is perceived with threat and superiority. This article recommends internal factors as drivers of a country's foreign policy.Keywords: NEW START; Russia; US; Foreign Policy.